The Degree of Including the Linguistic performance in Arabic Language Curricula: Analytical Study. - Bani-Yaseen, Mohammad Fawzy; Alqadi, Haitham Mamdouh (Latakia University Journal - Arts and Humanities Sciences Series, 2017)
This study aimed at analyzing the level of involvement of the linguistic performance in Arabic language curricula, represented by language skills: listening, conversation, reading and writing, in accordance to the outcomes of teaching embodied in the objectives in order to keep an eye on the appropriateness of the content of the Arabic language curriculum for the predetermined objectives. The results of analysis showed the following: the percentage of representation of the content for listening comprehension for all grades is “80.75”; the percentage of representation of the content for writing skills for all grades is “84.3”; the percentage of representation of the content for conversation skills for all grades is “91.25”; the percentage of representation of the content for reading comprehension for all grades is “92.8”. The results of analysis on the level of curriculum showed that: the percentage of representation of the content for all skills for the first grade is “89.5”; the percentage of representation of the content for all skills for the second grade is “89.125”; the percentage of representation of the content for all skills for the third grade is “87.875”; the percentage of representation of the content for all skills for the fourth grade is “87.375”; the percentage of representation of the content for all skills for the fifth grade is “85.5”; the percentage of representation of the content for all skills for the sixth grade is “84.375”. The study concluded with a number of recommendations.